(untitled) - Ridley, Diana (London, 2012)
This Second Edition of Diana Ridley′s bestselling guide to the literature review outlines practical strategies for reading and note taking, and guides the reader on how to conduct a systematic search of the available literature, and uses cases and examples throughout to demonstrate best practice in writing and presenting the review. New to this edition are examples drawn from a wide range of disciplines, a new chapter on conducting a systematic review, increased coverage of issues of evaluating quality and conducting reviews using online sources and online literature and enhanced guidance in dealing with copyright and permissions issues.
Keywords: Research,Nghiên cứu; Methods,Phương pháp